Treatment options for managing atherogenic dyslipidemia and fatty liver disease. (June 2014) - Rizzo, Manfredi; Montalto, Giuseppe; Al-Rasadi, Khalid
Abstract : Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in Western countries with up to 30% of the population affected. Since NAFLD is associated with an increased risk of cardiovascular (CV) disease, these patients should be stratified for CV risk factors, including atherogenic dyslipidemia, and managed accordingly. Lifestyle modifications represent an effective treatment for NAFLD, since most patients are overweight or obese. Also, promising, but not conclusive, results are available for current pharmacologic treatment. Drugs potentially effective against NAFLD include insulin sensitisers as well as fibrates and omega-3 polyunsaturated fatty acids, while there is reluctance to use statins in patients with suspected or established chronic liver disease. Several other therapeutic options are potentially available, and more data are expected from new peroxisome proliferator-activated receptor agonists and incretin-based therapies.